Complementary neural correlates of motivation in dopaminergic and noradrenergic neurons of monkeys - Bouret, Sebastien; Richmond, Barry J.; Ravel, Sabrina (Frontiers in Behavioral Neuroscience, 2012)
Rewards have many influences on learning, decision-making and performance. All seem to rely on complementary actions of two closely related catecholaminergic neuromodulators, dopamine and noradrenaline. We compared single unit activity of dopaminergic neurons of the substantia nigra pars compacta and noradrenergic neurons of the locus coeruleus in monkeys performing a reward schedule task. Their motivation, indexed using operant performance, increased as they progressed through schedules ending in reward delivery. The responses of dopaminergic and noradrenergic neurons around the time of major task events, visual cues predicting trial outcome and operant action to complete a trial, were similar, in that they occurred at the same time. They were also similar in that they both responded most strongly to the first cues in schedules, which are the most informative cues. The neuronal responses around the time of the monkeys’ actions were different, in that the response intensity profiles changed in opposite directions. Dopaminergic responses were stronger around predictably rewarded correct actions whereas noradrenergic responses were greater around predictably unrewarded correct actions. The complementary response profiles related to the monkeys operant actions suggest that dopamine neurons might relate to the value of the current action whereas the noradrenergic neurons relate to the psychological cost of that action.